2007
DOI: 10.1177/1934578x0700200206
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Comparison for Differentiation of Boswellia Carterii and B. Serrata

Abstract: Frankincense (Boswellia carterii) and olibanum (B. serrata) were chemically analyzed to determine compounds that would enable the differentiation of the two products. Typical compounds for both species were identified. Three new compounds, 24-noroleana-3,9(11),12-triene, 24-norursa-3,9(11),12-triene, and 24-norursa-3,12-diene-11-one, were identified in olibanum; these may be either naturally occuring or pyrolytic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
3
1
Order By: Relevance
“…Isolation of incensole and its acetate has been reported by a few authors from B. carterii [11,[21][22][23][24][25][26]. Nonetheless, we could not detect compounds 1 and 2 together in B. carterii, B. sacra and B. serrata.…”
contrasting
confidence: 53%
“…Isolation of incensole and its acetate has been reported by a few authors from B. carterii [11,[21][22][23][24][25][26]. Nonetheless, we could not detect compounds 1 and 2 together in B. carterii, B. sacra and B. serrata.…”
contrasting
confidence: 53%
“…2 Due to their interesting biological activities and varied structural patterns, incensole (1) and its acetate (2) have received special attention with respect to their isolation and synthesis. Incensole (1) was first reported by Corsano and Nicoletti 3 in 1967 3 from Boswellia carterii Birdw followed by later reports from the same species [4][5][6][7][8][9][10] as well as from B. papyrifera. 10 Due to the biological importance of incensole (1), two independent total syntheses have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Incensole (1) was first reported by Corsano and Nicoletti 3 in 1967 3 from Boswellia carterii Birdw followed by later reports from the same species [4][5][6][7][8][9][10] as well as from B. papyrifera. 10 Due to the biological importance of incensole (1), two independent total syntheses have also been reported. 11,12 In the present work, incensole acetate (2) was prepared on large-scale following Jauch's protocol, 11 using crude extracts of the Boswellia papyrifera Hochst.…”
Section: Introductionmentioning
confidence: 99%
“…; Modugno, Ribechini & Colombini ; Hanuš et al . ). The analyses conducted on the substance revealed that it did not belong to compounds of these two resins.…”
Section: Discussionmentioning
confidence: 97%